Determination of sulfonate ester genotoxic impurities in imatinib mesylate by gas chromatography with mass spectrometry. Issue 18 (7th September 2016) - Zhang, Chaozheng; Huang, Lin; Wu, Zhiguo; Chang, Chuanyou; Yang, Zhidong
Abstract : Methyl methanesulfonate and ethyl methanesulfonate are potential genotoxic impurities in imatinib mesylate. In this work, a simple, sensitive, reliable, and fast gas chromatography with mass spectrometry method for the simultaneous determination of methyl methanesulfonate and ethyl methanesulfonate was developed and validated. Total analysis time was only 7 min. An n ‐hexane/water solution was used to dissolve samples, and then extracted‐ion‐chromatogram mode was used to quantify methyl methanesulfonate and ethyl methanesulfonate. Calibration curves showed good linearity over the studied range for methyl methanesulfonate and ethyl methanesulfonate. The correlation coefficient of fit exceeded 0.999 for each impurity. The LOD and LOQ of methyl methanesulfonate and ethyl methanesulfonate were as low as 0.001 and 0.005 μg/mL, respectively, with RSDs of the peak area within 1.06–1.96%. Method accuracy was within 97.2–99.8% for methyl methanesulfonate and ethyl methanesulfonate. Therefore, this method can be used to quantify methyl methanesulfonate and ethyl methanesulfonate impurities at extremely low levels in imatinib mesylate.